2009
DOI: 10.1111/j.1600-0404.1994.tb01629.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurological and neuropsychiatric dysfunction in primary Sjögren's syndrome

Abstract: In a prospective clinical investigation of 20 patients with primary Sjögren's syndrome (SS), neurological complications, not attributable to other diseases were detected in 14 patients (= 70%). Dysfunction of the peripheral nervous system (PNS) was nearly twice as frequent as central nervous system (CNS) complications. PNS involvement was dominated by symmetric sensory neuropathies, carpal tunnel syndromes, cranial nerve palsies (above all trigeminal sensory neuropathy) and pupillary dysfunction. CNS impairmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(38 citation statements)
references
References 16 publications
3
31
0
3
Order By: Relevance
“…As Table 2 shows in items 2,4,5 and 6 of RAVLT test the difference between controls and PSS patients was close to the significance level (borderline). We believe that a larger sample could help understand the difference between the performance of PSS and healthy controls in other parts of the test; thus, confirming that PSS Brazilian patients show critical memory impairment, as presented in other studies 22,18,23 .…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…As Table 2 shows in items 2,4,5 and 6 of RAVLT test the difference between controls and PSS patients was close to the significance level (borderline). We believe that a larger sample could help understand the difference between the performance of PSS and healthy controls in other parts of the test; thus, confirming that PSS Brazilian patients show critical memory impairment, as presented in other studies 22,18,23 .…”
Section: Discussionmentioning
confidence: 48%
“…Memory and executive function are the most common cognitive alterations observed in PSS 22,18,23 . In the present study, we found a significant difference in cognitive performance between PSS patients and controls in conceptual flexibility (i.e., inhibition control), one aspect of executive function.…”
Section: Discussionmentioning
confidence: 99%
“…A broad spectrum of abnormalities have been described, with reported prevalence ranging from 1% to 46% (74,(107)(108)(109)(110) Central nervous system inflammatory disease, cognitive disorders, movement disorders and meningoencephalitis are described in more detail. Multiple sclerosis is an inflammatory disease of the nervous system for which no test is pathognomonic (15).…”
Section: Central Nervous System Manifestationsmentioning
confidence: 99%
“…На МРТ головного мозга у таких пациентов определяется муль-тифокальное очаговое поражение, а по данным SPECT -гипоперфузия, даже при отсутствии изменений. КН харак-теризуются снижением внимания, быстроты вербальной продуктивности, нарушением исполнительных функций, а деменция в этих случаях -преимущественно субкортикаль-ная или мультиинфарктная [36][37][38].…”
unclassified